Design of waste stabilization ponds for dairy processing plants in Uganda - Menya, E.; Wangi, G. M.; Amanyire, F.; Ebangu, B. (CIGR Journal, 2013)
Waste stabilization ponds (WSP) were designed to treat 287.5 m3 day-1 of wastewater generated from processing of 100 m3 of milk per day. The design involved use of existing models including those developed by Mara to size the anaerobic, facultative and maturation ponds. The design temperature was 250C. The anaerobic pond was designed based on volumetric organic loading rate while facultative pond was designed based on surface loading rate. On the other hand, the maturation pond was designed based on the number of coliform bacteria removed per 100 mL of wastewater. The anaerobic pond was designed to remove 70% BOD, facultative pond-75% and maturation pond-25% BOD. In addition, the maturation pond was designed to have a coliform bacteria removal efficiency of at least 99%. The total land requirement for anaerobic pond was estimated at 945.19 m2, facultative pond-6361.54 m2 and three maturation ponds-2709.06 m2. To cater for pond operation and maintenance, an additional 25% land was incorporated resulting into 1.25 hectares as the total land area required for pond construction, operation and maintenance. Besides treatment of wastewater to reduce BOD, remove pathogens and other pollutants, the use of WSP can result into high economic benefits through recycling of wastewater for agriculture and aquaculture. As a result, the payback period for the investment cost may also be shortened.
Keywords: Milk; Waste stabilization ponds; BOD; Anaerobic; Facultative; Maturation